Perpanjangan Masa Jabatan Pimpinan Komisi Pemberantasan Korupsi Republik Indonesia Berdasarkan Putusan Mahkamah Konstitusi Nomor 112/PUU-XX/2022 - Betekeneng, Anshari; Nendissa, Renny Heronia; Irham, Muhammad (CAPITAN: Constitutional Law & Administrative Law Review, 2024)
Review of Law No. 19 of 2019 concerning the Second Amendment to Law No. 30 of 2002 concerning the Corruption Eradication Commission. Constitutional Court Decision No. 112/PUU-XX/2022 whose decision accepts all of the applicant's requests. The Constitutional Court is not a fully democratic state institution, because the people do not directly elect the members of the court, and the term of office is more or less closely related to the domain of formulating open legal policy. The leadership of any institution in terms of extending its term of office must be carried out through the law-making council, namely the legislative body. Because officially this institution is appointed as the people's representative, including having a process of public participation. Changes to the terms of office from 4 years to 5 years, as in Law No. 30 of 2002 Article 34, during the process of changing the extension of the term of office of a state institution, it should be given to state institutions that have involvement in the process of drafting Legislative Regulations, which in turn expressly stated in the 1945 Constitution. This normative juridical research was carried out using a statutory approach, conceptual approach and case approach. In its decision, the Constitutional Court made new norms that are regulatory in nature and do not take into account the opinions of the People's Representative Council and the Government, which is an abuse of authority or is done arbitrarily and exceeds the authority of the legislators. This decision is contrary to the 1945 Constitution of the Republic of Indonesia Article 5 Articles 20 and 28 I. As a result of the Constitutional Court's decision being retroactive, problematic and subject to multiple interpretations, if there are parties who justify the decision regarding the existence of the leadership of the Corruption Eradication Commission while in office, theoretically it is feared that it will trigger another petition.